스파크점화 엔진에서 압축비에 따른 프로판과 부탄의 연소 분석 - 박현욱; Hyunwook Park; 이준순; Junsun Lee; 오승묵; Seungmook Oh; 김창업; Changup Kim; 이용규; Yonggyu Lee; 강건용; Kernyong Kang (한국분무공학회지, 2022)
Combustion and performance of a spark-ignition engine fueled with propane and butane were analyzed under different compression ratio. The electricity efficiencies of propane and butane increased with increasing the electricity production. The heat release rates of propane and butane were similar at a compression ratio of 9:1 because both fuels had similar optimal ignition timings without knocking combustion. Therefore, the difference in electricity efficiencies of engine generators was insignificant. However, at a higher compression ratio of 11:1, the butane engine generator had a lower electricity efficiency than the propane engine generator because its ignition timing retarded to suppress the knocking combustion.